Analysis of the community behavioural patterns in management of household plastic waste due to the COVID-19 pandemic in Sri Lanka. (December 2022) - Jayasinghe, Rohantha Rukshan; Abeyrathna, Wasudha Prabodhani; Lythgoe, Daniel; Hendawitharana, Manuja Promodya; Liyanage, Champika; Williams, Karl; Halwatura, Rangika Umesh
Abstract: The COVID-19 pandemic has adversely affected human lifestyle in numerous ways and one such key affected social element is the management of household plastic waste. Due to its effective barrier properties against the COVID-19 virus, usage and consumption of personal protective equipment (PPE) and other single-use plastic (SUP) products have increased exponentially to meet the accelerated demand. Therefore, this paper analyses the changes in community behavioural patterns of household plastic waste management with the prevailing COVID-19 pandemic situation in Sri Lanka. The comparative analysis of majorly consumed plastic waste types, plastic disposal methods, and perceptions of existing policies before and after the pandemic are broadly discussed. A comprehensive questionnaire was conducted in a stratified randomly sampled community and analysed using SPSS. Disposable face masks (39.9%) and hand sanitiser products (33.0%) were popular plastic products during the pandemic. The frequency of handing over the waste to collectors and recycling centres decreased slightly, from 32.1% to 31.4% and 24.2%–19.8%, respectively. Conversely, respondents' preference for burning plastic waste increased from 23.4% to 27.0% after the pandemic. The plastic disposal methods from before and after the pandemic are significantly associated with income level ( p = 0.00) and employment status ( p = 0.00). No significant association was observed between the disposal method before the pandemic and the education level of respondents ( p = 0.185). However, a significant association was evident between the disposal method after the pandemic and the education level of respondents ( p = 0.025). Graphical abstract: Image 1